2012
DOI: 10.1007/s13364-012-0073-1
|View full text |Cite
|
Sign up to set email alerts
|

Trace metals and micronutrients in bone tissues of the red fox Vulpes vulpes (L., 1758)

Abstract: In this study we determined the levels of trace elements (zinc, copper, lead, cadmium and mercury) in three layers of bones of the hip joint (cartilage, compact bone and spongy bone) of 30 red foxes (Vulpes vulpes) from north-western Poland. Concentrations of Cu, Zn, Pb and Cd were determined by atomic absorption spectrophotometry (ICP-AES) in inductively coupled argon plasma using a Perkin-Elmer Optima 2000 DV. Determination of Hg concentration was performed by atomic absorption spectroscopy. In cartilage, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
(53 reference statements)
1
13
0
Order By: Relevance
“…For example, high Hg content in kidneys (5.11 mg/kg dry matter (DM)), in liver (4.52 mg/kg), and in muscles (1.56 mg/kg) was noted in juvenile V. vulpes inhabiting Mielin Island in North-West Poland (Kalisinska et al 2009). Low Hg concentration in bones (0.002 mg/kg DM on average) was revealed in other study on V. vulpes (Lanocha et al 2012). These authors claim also that the tissues and organs of free living V. vulpes are good bioindicators of environment pollution with Hg and other toxic metals like e.g.…”
Section: Introductionmentioning
confidence: 66%
“…For example, high Hg content in kidneys (5.11 mg/kg dry matter (DM)), in liver (4.52 mg/kg), and in muscles (1.56 mg/kg) was noted in juvenile V. vulpes inhabiting Mielin Island in North-West Poland (Kalisinska et al 2009). Low Hg concentration in bones (0.002 mg/kg DM on average) was revealed in other study on V. vulpes (Lanocha et al 2012). These authors claim also that the tissues and organs of free living V. vulpes are good bioindicators of environment pollution with Hg and other toxic metals like e.g.…”
Section: Introductionmentioning
confidence: 66%
“…In the compact bone tissue reported, the results showed 0.0054 mg/kg dw (ranges 0.0012 – 0.0226) and 0.012 mg/kg dw (ranges nd – 0.038) respectively (Lanocha et al 2012 and Millan et al 2008). This is in the same range as our Alaskan red foxes reporting mean THg for compact bone as 0.004 mg/kg with a range of 0.001 to 0.010 mg/kg (Table 2).…”
Section: Discussionmentioning
confidence: 94%
“…Two European studies reported on THg concentrations that were found in wild red fox bones (Lanocha et al 2012; Millan et al 2008). In the compact bone tissue reported, the results showed 0.0054 mg/kg dw (ranges 0.0012 – 0.0226) and 0.012 mg/kg dw (ranges nd – 0.038) respectively (Lanocha et al 2012 and Millan et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These species meet a number of criteria for bioindicators and show a measurable response to environmental pollutants, as documented in the works of various authors [3, 4, 710]. Researchers usually determine trace elements in their kidneys and liver, key organs in detoxification; bones are examined much less frequently [5, 7, 9, 11–13]. …”
Section: Introductionmentioning
confidence: 99%